Political, legal and religious conflict in Montenegro - genesis, course, last clash - Ickiewicz-Sawicka, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Contemporary Montenegro was created as a result of the break-up of the Socialist Federal Republic of Yugoslavia. Although this country was for a short time an integral part of Serbian Republic and functioned on the international arena as the so-called new Yugoslavia, Montenegrin society decided in a referendum to proclaim independence in 2006. Despite the fact that the separation took place in a peaceful manner, the frozen conflict between these countries slowly began to intensify. The areas it covered were legal, political and especially religious issues.
Keywords: Montenegro; nation; ethnic group; conflict; law; politics; religion